The causal relationship between gut microbiota and lower extremity deep vein thrombosis combined with pulmonary embolism - Qiyang Xu; Jihong Fang; Yi Wang; Dehai Lang; Bin Xu (Frontiers in Microbiology, 2024)
BackgroundOver the years, numerous studies have explored the relationship between gut microbiota and lower extremity deep vein thrombosis (LEDVT) and pulmonary embolism (PE). The present study utilized Mendelian randomization (MR) to assess the causal link between gut microbiota and LEDVT combined with PE.MethodsHuman gut microbiota genome-wide association study (GWAS) summary data from the MiBioGen consortium (n = 18,340) were utilized. Summary-level data on LEDVT (2,116 cases and 359,078 controls) and LEDVT combined with PE (4,319 cases and 356,875 controls) were obtained from the IEU Open GWAS project. MR analysis was conducted using the inverse variance weighted (IVW) method as the primary analysis. Additionally, MR-Egger, weighted median, weighted mode, and simple mode were employed as supplementary methods. Sensitivity analyses, including tests for heterogeneity and horizontal pleiotropy, were performed. Lastly, reverse MR analysis was performed.ResultsThe IVW analyses revealed seven causal relationships between genetic liability in the gut microbiota and LEDVT and five causal relationships between genetic liability in the gut microbiota and LEDVT combined with PE. The intersection of these outcomes identified that the genus Butyricicoccus reduced the risk of both LEDVT and LEDVT combined with PE, while the genus Clostridium innocuum increased the risk for both conditions.ConclusionThis study demonstrates that the gut microbiota is causally associated with LEDVT and LEDVT combined with PE. Our findings provide valuable insights into the underlying mechanisms and suggest potential avenues for further clinical investigations of these conditions.